The Distribution of Sarcocsytis Species Described by Ungulates-Canids Life Cycle in Intestines of Small Predators of the Family Mustelidae - Šneideris, Donatas; Moskaliova, Darija; Butkauskas, Dalius; Prakas, Petras (Acta parasitologica, 2024)
Purpose Using molecular techniques, we have previously shown that carnivorous mammals of the family Mustelidae might be common definitive hosts for various protozoan Sarcocystis species. In the present study we aimed to unravel whether Sarcocystis species using ungulates as intermediate hosts and canids or felids as definitive hosts can be found in intestine of mustelids. Methods Small intestine samples of 93 individual mustelids of five different species from Lithuania were examined. Sarcocystis species were identified based on species-specific PCR and subsequent cox1 sequencing. Results Six Sarcocystis species ( S . arieticanis , S . bertrami , S . capracanis , S . capreolicanis , S . linearis and S . morae ) defined by ungulate-canid life cycle were detected for the first time in small intestines of mustelids. By contrast, the prevalence of Sarcocystis characterised by ungulate-felid life cycle was low (3.2%). Overall, 76% of the examined animals were positive for at least one of the studied Sarcocystis species. Four species, S. arieticanis , S. bertrami , S. capracanis and S. morae were most commonly found, with the detection rate of about 40%. Conclusions The current finding, in addition to our previous studies, suggests that mustelids play an important role in the spread of various Sarcocystis species.